Kinetic selectivity dictates the construction of cancer cell-targeting enzyme instructed supramolecular assemblies. (December 2022) - Tian, Falin; Yang, Min; Yao, Qingxin; Song, Jialei; He, Jianxin; Shi, Xinghua; Gao, Yuan
Abstract: The in situ construction of nanomaterials such as intracellular enzyme instructed supramolecular assemblies (EISA) has shown broad biomedical applications. The EISA is a multi-step process in which enzymatic conversion firstly converts precursors into hydrogelators, followed by supramolecular assembly to form nanostructures. In this process, for given hydrogelator with certain assembly propensity, the initial concentration of the corresponding precursor is critical for the formation of intracellular assemblies, which has not been quantitatively assessed due to the lack of proper theoretical model and accurate parameters. Here, based on recent development of a thermodynamic model, we investigate the assembly kinetics of EISA formation within targeted living cells. By establishing a time-resolved photoluminescence spectroscopy framework, we obtain the fluorescence lifetimes assigned to monomers and assemblies, and decouple the disassembly and assembly kinetics. The obtained (dis)assembly kinetics, combined with the enzymatic transformation kinetics, form the basis for the cell-selective accumulation of EISA in a plane of initial precursor concentration and cellular enzyme activity, namely S 0 M - k c E 0 . The kinetic selectivity could provide an alternative to active and passive targeting, opening an avenue towards cancer-agnostic therapy by guiding the proper dosage of assembling precursors to construct cancer cell-targeting EISA. Graphical Abstract: ga1 Highlights: The resolution of dynamic transitions of fluorescence lifetime allowed the measurements of self-assembly kinetics parameters. The combination of assembly kinetic and enzymatic kinetics dictated the cell-selective formation of intracellular assemblies. The kinetic selectivity provided an alternative mechanism of targeting in non-equilibrium systems for cancer-agnostic therapy.